2017
DOI: 10.1007/s00162-017-0429-x
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent modeling of oscillatory instability of three-dimensional natural convection of air in a laterally heated cubic box

Abstract: Transition from steady to oscillatory buoyancy convection of air in a laterally heated cubic box is studied numerically by straight-forward time integration of Boussinesq equations using a series of gradually refined finite volume grids. Horizontal and spanwise cube boundaries are assumed to be either perfectly thermally conducting or perfectly thermally insulated, which results in four different sets of thermal boundary conditions. Critical Grashof numbers are obtained by interpolation of numerically extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 41 publications
(149 reference statements)
7
35
0
Order By: Relevance
“…The method is based on the finite-volume discretization scheme described in [29,30]. The electromagnetic part of the scheme has been added for the present study.…”
Section: Methods Imentioning
confidence: 99%
See 2 more Smart Citations
“…The method is based on the finite-volume discretization scheme described in [29,30]. The electromagnetic part of the scheme has been added for the present study.…”
Section: Methods Imentioning
confidence: 99%
“…The electromagnetic part of the scheme has been added for the present study. The method includes direct calculation of steady states done by Newton iterations as in [31] and integration of the governing equations in time as in [30] .…”
Section: Methods Imentioning
confidence: 99%
See 1 more Smart Citation
“…A unified perspective of instability in rotating Bödewadt, Ekman and von Kármán layers has been presented [7]. Instability of variable density flows in threedimensional containers has been analysed numerically [10,25] while a combined analytical and experimental effort discussed instability of compressible spanwise homogeneous cavity flow [31]. In the flow control theme, a linear feedback control approach was demonstrated to reduce the pressure drag of a D-shaped bluff body [6] and cluster-based control of a separating flow over a smoothly contoured ramp has been discussed [14].…”
Section: Contributions To the Present Volumementioning
confidence: 99%
“…Results show that the Nusselt number increases with the increasing heater size and the Rayleigh number (Cianfrini et al, 2013). Three-dimensional numerical studies reported multiple states and bifurcations on natural convection in a rectangular cavity with partially heated vertical walls (Gelfgat, 2017). The study of natural convection has been extended to nanofluids (Nascimento et al, 2019).…”
Section: Introductionmentioning
confidence: 99%